Poly (3-hexylthiophene) nanofibers for organic photovoltaics application - Sun, Shuangyong. (2009)
Bulk heterojunction (BHJ) organic photovoltaic (OPV) cell based on poly (3-hexylthiophene):[6, 6]-phenyl-C60-butyric acid methyl ester (P3HT:[C61]-PCBM) which shows high power conversion efficiency (PCE) of 5% has attracted a lot of attention from both industrial and scientific communities. However, to get high PCE heat treatment is necessary to increase P3HT crystallinity. It is facile to get high P3HT crystallinity by preassembling P3HT into nanofiber before mixing with PCBM. In this project, P3HT nanofibers have been grown in solution by whisker method and their role in BHJ OPV system was investigated. Various parameters for P3HT-nanofiber growth, such as solvent choice, P3HT concentration, cooling rate as well as ageing time, were found to be critical to obtain high quality P3HT nanofibers. For photovoltaic device application, it is confirmed that optimization of donor-acceptor ratio and film thickness are necessary to ensure good device performance. We obtained a maximum power conversion efficiency (PCE) of 3.136 % achieved at 1:1 donor-acceptor blend ratio when measured under illumination of AM 1.5 light with intensity of 100 mW cm-2. The P3HT nanofiber was also successfully integrated with either thermal annealing or solvent additive approach to achieve even higher device efficiency. The highly ordered structures, as confirmed by UV-Vis and AFM characterization techniques, are believed to induce high hole mobility in the blend system leading to improved performance. Finally, this project has successfully investigated the role of P3HT nanofibers in improving the efficiency of P3HT:PCBM OPV devices and initiate a thermal-free method for the fabrication of OPV devices on flexible substrates.